Current Injection‐Induced Performance Enhancement in n‐Type Silicon Heterojunction Solar Cells. Issue 11 (21st July 2022) - Yang, Lei; He, Qiyuan; Hu, Zechen; Yu, Xuegong; Yang, Lifei; Yang, Deren
Abstract : Silicon heterojunction (SHJ) solar cells have garnered significant attention recently due to their excellent performance, benefiting from the outstanding passivation quality of intrinsic/doped hydrogenated amorphous silicon ( a ‐Si:H) bilayers. Herein, it is found that current injection at elevated temperatures can enhance the electrical performance of SHJ solar cells. The kinetics study clarifies that activation energy of 0.5 eV is obtained for this enhancement phenomenon. By using photoluminescence (PL) images, it is demonstrated that the performance enhancement can be mainly attributed to the reduction of electrically active defects. The underlying mechanism is focused on the diffusion and passivation effect of hydrogen, which could be valuable for understanding the kinetics of the current injection‐induced enhancement phenomenon in the SHJ cells. This approach serves as an alternative method of light soaking to reach the effect of performance enhancement of SHJ cells, making it more competitive in the photovoltaics industry. Abstract : In this article, it is found that current injection at elevated temperatures can enhance the performance of the silicon heterojunction (SHJ) solar cells. The underlying mechanism is focused on the diffusion and passivation effect of hydrogen. It is valuable for understanding the kinetics of the current injection‐induced enhancement phenomenon in SHJ cells.